The Role of Interpersonal Communication in Employee Relationships at STIE Yasa Anggana - Mardianti, Fera; Ulfaturrohman, Nur Hidayah; Rosmiati, Mia; Setiawan, Wawan Lulus (Finance and Business Management Journal, 2025)
This study aims to analyze the role of interpersonal communication in building relationships between individual employees (staff) at STIE “Yasa Anggana” Garut. Using a descriptive qualitative approach through in-depth interviews, observation, and documentation of 13 informants from various work units, this study explores the forms of interpersonal communication, factors that influence its effectiveness, and obstacles that arise in work interactions. The analysis uses indicators of interpersonal communication effectiveness according to Joseph A. DeVito, namely openness, empathy, support, positive attitude, and equality. The results of the study indicate that interpersonal communication plays a significant role in building harmonious work relationships, improving coordination, and strengthening emotional bonds between employees. However, various obstacles were found such as a lack of information transparency, the dominance of informal communication, emotional sensitivity, and minimal support between units. This study confirms that effective interpersonal communication is an important foundation for creating collaboration and a positive work climate in the campus environment. These findings are expected to be the basis for improving formal communication practices, increasing interpersonal competence, and strengthening a supportive work culture.